HUBUNGAN KONTRAK PSIKOLOGIS DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Firdaus; Anisah (JUMANJI (JURNAL MANAJEMEN JAMBI), 2024)
his research aims to examine the influence of the psychological contract on organizational commitment and the influence of both on employee performance. The research method used was a quantitative descriptive method with a sample of 93 banking employees in Jambi City. The data collection technique used in this research is a questionnaire and the data analysis technique uses the SEM PLS method. The results of this research prove that there is a positive and significant influence of psychological contracts on organizational commitment and organizational commitment on employee performance, however, psychological contracts only have an indirect influence on employee performance through organizational commitment.